2015
DOI: 10.1093/nar/gku1382
|View full text |Cite
|
Sign up to set email alerts
|

Two novel NAC transcription factors regulate gene expression and flowering time by associating with the histone demethylase JMJ14

Abstract: The histone demethylase JMJ14 catalyzes histone demethylation at lysine 4 of histone 3 and is involved in transcriptional repression and flowering time control in Arabidopsis. Here, we report that JMJ14 is physically associated with two previously uncharacterized NAC transcription factors, NAC050 and NAC052. The NAC050/052-RNAi plants and the CRISPR-CAS9-mediated nac050/052 double mutant plants show an early flowering phenotype, which is similar to the phenotype of jmj14, suggesting a functional association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 52 publications
0
90
0
Order By: Relevance
“…Recent reports show that some NAC transcription factors are also involved in flowering-time regulation (Ning et al 2015;Yoo et al 2007). Among them, NAC050 and NAC052 were reported to function as negative regulators of flowering (Ning et al 2015). Similarly to anac075 mutants, loss-offunction lines of NAC050/NAC052 flower early under both long-and short-day conditions.…”
Section: Anac075 Did Not Interact With a Histone Demethylase Jmj14mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent reports show that some NAC transcription factors are also involved in flowering-time regulation (Ning et al 2015;Yoo et al 2007). Among them, NAC050 and NAC052 were reported to function as negative regulators of flowering (Ning et al 2015). Similarly to anac075 mutants, loss-offunction lines of NAC050/NAC052 flower early under both long-and short-day conditions.…”
Section: Anac075 Did Not Interact With a Histone Demethylase Jmj14mentioning
confidence: 99%
“…Loss of function of JMJ14, a JmjC-domain containing histone demethylase, leads to early flowering under both long-and short-day conditions, and overexpression of JMJ14 (JMJ14-ox) leads to late flowering, indicating that JMJ14 functions as a floral repressor (Jeong et al 2009;Lu et al 2010;Ning et al 2015;Searle et al 2010;Yang et al 2010). jmj14 under short days flowers considerably later than that under long days, suggesting that the mutants retain photoperiod sensitivity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, AtJMJ14, an active histone H3K4 demethylase (Lu et al, 2010; Yang et al, 2010), was also implicated in preventing early flowering by repressing the expression of FLOWERING LOCUS T ( FT ) and its homologs. Recently, Ning reported that AtJMJ14 associates with two NAC transcription factors, NAC050 and NAC052, and co-occupies hundreds of common target genes, resulting in H3K4 demethylation and transcriptional repression (Ning et al, 2015). Apart from controlling flowering time, there is also evidence that AtJMJ14 functions in RNA silencing and cell-to-cell movement of an RNA silencing signal (Lu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%